Two new species of Syllidae (Annelida: Polychaeta) from DIVA-Artabria I project (cruise 2002) to deep areas off NW Spain - Lucas, Yolanda; San Martín, Guillermo; Parapar, Julio (Zootaxa, 2012)
Based on material collected during the DIVA-Artabria I project (2002 cruise) from deep areas (629–1132m) of the shelfand upper slope off the Ártabro gulf (Galicia, NW Spain), two new species of Syllidae (Annelida: Polychaeta) are de-scribed. Eurysyllis mercuryi sp. nov. is characterized by having compound chaetae with elongated blades, provided withlong spines, and Syllis mercedesae sp. nov. is diagnosed by the possession of a unique combination of straight aciculae,protruding from parapodial lobes in posterior-most chaetigers, and moderately long spiniger-like chaetae in midbody pro-vided with indistinct subdistal tooth, appearing almost unidentate. Eurysyllis mercuryi sp. nov. is the fifth species of the genus described worldwide and the second reported species in European waters after E. tuberculata Ehlers, 1864.